2015
DOI: 10.1155/2015/743621
|View full text |Cite
|
Sign up to set email alerts
|

Successful Delivery of Twin Pregnancy in Class U3b/C2/V1 Uterus by Bilateral Caesarean Section after Spontaneous Conception

Abstract: A case of a 19-year-old female with class U3b/C2/V1 uterus conceived a twin pregnancy with a fetus in each horn after spontaneous conception. She referred to our department with presentation of premature rupture of membranes, with a history of cesarean delivery of a single full term living fetus a year and a half before this delivery. Examination revealed two completely separate uterine horns with a fetus in each horn, two distinct externally rounded cervices, and a single vagina with a short nonobstructing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…In the current case, the babies were delivered by a double lower segment caesarean section. Twin pregnancies with uterine malformations have a high rate of miscarriage [4], but in the present case, there were no complications and the babies were delivered safely. In some cases, cervical circlage has been tried to prevent the pre-term delivery.…”
Section: Discussioncontrasting
confidence: 53%
“…In the current case, the babies were delivered by a double lower segment caesarean section. Twin pregnancies with uterine malformations have a high rate of miscarriage [4], but in the present case, there were no complications and the babies were delivered safely. In some cases, cervical circlage has been tried to prevent the pre-term delivery.…”
Section: Discussioncontrasting
confidence: 53%
“…At around the 20th week, the septum is reabsorbed, and an arrest in this reabsorption results in uterus didelphus. [4] A systematic review of 3805 women with uterine malformations and a singleton pregnancy showed that those with a uterus didelphys had an increased risk of first trimester miscarriage (RR 1.1), second trimester miscarriage (RR 1.39), preterm birth (RR 3.58) and malpresentation at delivery (RR 3.7) . [5] Such statistics for dicavitary twin cases are currently unknown.…”
Section: Discussionmentioning
confidence: 99%